Viferon Suppositoria in Therapy of Relapsing Herpesvirus Infection in Women - A. N. Vasilyev; ZN. A. Kagramanova; V. V. Malinovskaya; V. V. Parfenov (Антибиотики и Химиотерапия)
The therapeutic efficacy of Viferon, a recombinant human interferon alpha-2b (rectal suppositoria) was studied in the therapy of relapsing herpesvirus infection in women. The clinical efficacy of the drug was recorded in 90% of the patients. The analysis of the remote results of the treatment made it possible to conclude that the Viferon suppositoria had an antirelapsing activity.